The Effectiveness of Problem Based Learning (PBL) Method Through Marquee Model to Cultivate Literacy - Diastuti, Indah Mei; Sulton, Agus (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2020)
The aim of this study was to determine the effectiveness of the Problem Based Learning (PBL) method to cultivate students’ literacy. By using the marquee model, the students can focus on writing which would be the topic of problems that would be discussed through the PBL method. The method used a quasi experimental design. The result of this research showed that PBL method through Marquee media was effective to improve the literacy culture of students at Universitas Hasyim Asy’ari (UNHASY) Tebuireng Jombang. The literacy culture before using PBL method through Marquee was 75% of children rarely do literacy activities. After using PBL method through Marquee was 90% children often do literacy activities. Hence, it can be concluded that the problem basic learning (PBL) method through marquee can improve the students’ literacy culture of Indonesian language and literature education, mathematics education. Because there was an increase from 75% to 90% of students who like to read, this indicates that PBL through marquee was effective in improving literacy culture. Keyword: Problem Based Learning, Marquee Model, Cultivate Literacy